Wastewater microbiology - Bitton, Gabriel (Hoboken, N.J. : Wiley-Blackwell, 2011)
"Wastewater Microbiology focuses on microbial contaminants found in wastewater, methods of detection for these contaminants, and methods of cleansing water of microbial contamination. This classic reference has now been updated to focus more exclusively on issues particular to wastewater, with new information on fecal contamination and new molecular methods. The book features new methods to determine cell viability/activity in environmental samples; a new section on bacterial spores as indicators; new information covering disinfection byproducts, UV disinfection, and photoreactivation; and much more" --Provided by publisher.
Includes bibliographical references and index.
Keywords: Sanitary microbiology; Water -- Microbiology; Sewage -- Microbiology